A Dual-band Microstrip Slotted Antenna for UHF and Microwave RFID Readers - Ahmed El Hamraoui; El Hassane Abdelmounim; Jamal Zbitou; Laarbi Elabdellaoui; Hamid Bennis; Mohamed Latrach (Universitas Ahmad Dahlan, 2018)
In this paper a new and simple dual-band microstrip slot antenna design combined with two inverted L-shaped slots integrated in the radiating patch is presented. This antenna is suitable for operating at 915 MHz and 2.45 GHz in order to cover the Radio Frequency Identification (RFID) frequencies bands. By optimizing the structure design, good performances in term of return loss radiation pattern and efficiency are achieved. The simulation results were obtained by using ADS and CST Microwave Studio electromagnetic solvers. The proposed antenna is mounted on an FR4 substrate with dielectric permittivity constant 4.4, thickness of 1.6 mm and loss tangent of 0.025 and a total area of 48×47 mm2. The design methodology used to achieve the dual-band antenna and both experimental, simulated results are presented.